Restructuring Rental Rate Components to be More Innovative Sharia Compliance Product in Islamic Home Financing - Akhmad Afffandi Mahfudz; Nor Hayati Ahmad; Rosylin Mohd Yusoff; Asmadi Muhamad Naim; Turkhan Ali (European Journal of Islamic Finance, 2016)
This study attempts to restructure a more innovative Sharia compliant product in Islamic home financing. By examining the components of residential rental index and addressing some unresolved issues particularly in Musyarakah Mutanaqisah, the study seeks to propose rental index as an alternative benchmark to current interest rates. This paper employs library research derived from the pedigree of Islamic home financing. However, some mathematical modelings are employed to strengthen the analysis. The paper proposes a new structure of rental rate as a benchmark instead of the conventional interest rate in pricing of loans. This structure comprises of Islamic rental rates, risk premium, overhead expenses and profit margin. Our findings suggest that these components are better-able to capture the market conditions as compared to the element of interest in BLR (Base Lending Rate) as practiced by banking industry. This paper also recommends the solution for default payment and at the same time addresses inconsistencies of MM contract offered by Islamic banks. Since rental index is regarded as new approach in Islamic home financing, this study limits its scope with one contract namely musharakah mutanaqishah. This limitation might wreak different views from industries for implementation and thus needs to be further tested. The findings also reveal some future challenges in applying more innovative Sharia compliant approach since up to date, there are no general consensus derived from different schools of thought in resolving the issues of pricing in Islamic home financing. Islamic banks might be resistant in accepting this newly proposed structure of rental rate since it generates lesser amount of profits.